2016
DOI: 10.1039/c5qo00399g
|View full text |Cite
|
Sign up to set email alerts
|

A copper(i)-catalyzed three-component reaction of triethoxysilanes, sulfur dioxide, and alkyl halides

Abstract: A copper(i)-catalyzed three-component reaction of triethoxysilanes, DABCO·(SO2)2, and alkyl halides is reported. This transformation provides a facile route to sulfones under ligand-free conditions catalyzed by copper(i) oxide. The insertion of sulfur dioxide is efficient, and both triethoxyarylsilanes and triethoxyalkylsilanes are practicable during the coupling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Further evaluation of ligands revealed that 1,3-bis(diphenylphosphino)propane( dppp), triphenylphosphine and Xantphos furnished lower yields than 1,1'-ferrocenebis(diphenylphosphine) (dppf) ( Table 1, entries 8-10). Using tin instead of zinc as ar eductant dramatically increases the efficiencyo ft he formation of sulfone 3a (96 %yield, Table 1, entries [11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evaluation of ligands revealed that 1,3-bis(diphenylphosphino)propane( dppp), triphenylphosphine and Xantphos furnished lower yields than 1,1'-ferrocenebis(diphenylphosphine) (dppf) ( Table 1, entries 8-10). Using tin instead of zinc as ar eductant dramatically increases the efficiencyo ft he formation of sulfone 3a (96 %yield, Table 1, entries [11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…[8] Strategies for sulfone construction through the introduction of sulfur dioxide into organic frameworks is of great interest owing to its atom, step,a nd oxidation economy. [9] For example,the transition-metal-catalyzed syntheses of sulfones and sulfonamides from boronic acids [RB(OH) 2 ], [10] organolithium reagents (RLi), [11] Grignard reagents (RMgBr), [12] and organosilanes [RSi(OEt) 3 ] [13] have been well established by the groups of Toste,S havnya, Willis,W u, and Tu ,a nd these processes involve elegant couplings of organometallic reagents with organohalides. [14] Over the past few decades, direct reductive cross-couplings of distinct halides without ap re-formed organometallic reagent have been studied extensively (Scheme 2a-1).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated for the first time in 2015, the preparation of sulfones in a single step from SO 2 surrogates . Interestingly, air‐ and moisture‐stable organosilanes could also be used for the synthesis of sulfones using a copper(I) oxide as catalyst with SO 2 surrogates and alkylhalides . In order to circumvent the use of toxic organometallic reagents or metal catalysts, the preparation of sulfones under metal‐free conditions is still to be accomplished.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Because arylboronic acids are compatible with alkylhalides,Shavnya et al demonstrated for the first time in 2015, the preparation of sulfones in as ingle step from SO 2 surrogates. [8] In order to circumvent the use of toxic organometallic reagents or metal catalysts,t he preparation of sulfones under metal-free conditions is still to be accomplished. [8] In order to circumvent the use of toxic organometallic reagents or metal catalysts,t he preparation of sulfones under metal-free conditions is still to be accomplished.…”
mentioning
confidence: 99%
“…[6b] Interestingly,a ir-a nd moisture-stable organosilanes could also be used for the synthesis of sulfones using ac opper(I) oxide as catalyst with SO 2 surrogates and alkylhalides. [8] In order to circumvent the use of toxic organometallic reagents or metal catalysts,t he preparation of sulfones under metal-free conditions is still to be accomplished. With this perspective,w ereport herein the one-step fluoride-mediated synthesis of aryl and heteroarylsulfones from aryl and heteroarylsilanes under metal-free conditions.…”
mentioning
confidence: 99%